Effect of Current Density on Properties Of Nickel-Silicon Carbide Composites - Hama, Kailash; Nyachhyon, Armila Rajbhandari; Gyawali, Gobinda; Lee, Soo Wohn (Journal of Institute of Science and Technology, 2016)
Nickel-Silicon Carbide (Ni-SiC) composite coating has been prepared by two electrode electrochemical co-deposition technique in nickel sulfamate bath. The Cetyltrimethylammonium bromide (CTAB) was added in bath as cationic surfactant whereas saccharine as a grain modifier. The effect of current density during deposition was systematically studied and optimized to get homogeneous surface texture with utmost microhardness and deprived coefficient of friction. The result revealed that 60 mA/cm2 current density was found to be the optimum current density which showed the highest microhardness of 590 ± 10 Hv and lowest coefficient of friction with regular surface morphology. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, Page : 82-85